THE-X: Privacy-Preserving Transformer Inference with Homomorphic Encryption - Chen, Tianyu; Bao, Hangbo; Huang, Shaohan; Dong, Li; Jiao, Binxing; Jiang (姜大昕), Daxin; Zhou, Haoyi; Li, Jianxin; Wei, Furu (2022)
Abstract to come...